(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To describe the early hypoparathyroidism status and some related factors in patients after total thyroidectomy due to papillary thyroid cancer. Materials and method: A cross-sectional descriptive study on 118 patients with papillary thyroid cancer who underwent total thyroidectomy. The hypoparathyroidism status was assessed within the first 24 hours and after 3 months. Results: The rate of hypoparathyroidism within the first 24 hours after surgery was 16.9%, and at the 3-month mark, it was 3.4%. The risk of early hypoparathyroidism after surgery increased in patients with tumors larger than 20 mm compared to those with tumors ≤ 10 mm (OR=3.4, 95% CI 1.1-10.7; p < 0.05); in the group with capsular invasion compared to the group without capsular invasion (OR=3.7, 95% CI 1.3-10.5; p < 0.05); and in the group undergoing central + lateral neck lymph node dissection compared to those not undergoing lymph node dissection (OR=10, 95% CI 1.2-83.6; p < 0.05). Conclusion: The rate of hypoparathyroidism within the first 24 hours after total thyroidectomy for papillary thyroid cancer is high, especially in high-risk individuals.